The COVID-19 coronavirus outbreak: May 2020 update - Temte, Jonathan (Henry Stewart Talks, 2020)
What has changed in the understanding of COVID-19 epidemiology, Lessons learnt regarding containment, and the implications for future strategies, New information regarding immunity and clinical outcomes of the virus, Possible future scenarios